2016
DOI: 10.1088/0960-1317/26/10/104003
|View full text |Cite
|
Sign up to set email alerts
|

Optogalvanic spectroscopy with microplasma sources—current status and development towards a lab on a chip

Abstract: Söderberg, J. et al. (2016) Optogalvanic spectroscopy with microplasma sources -Current status and development towards lab on a chip. Journal of Micromechanics and MicroengineeringAccess to the published version may require subscription. N.B. When citing this work, cite the original published paper.Filen arkiveras tills dess att information om publikationen kommer in. Det är post-print och inga problem att ha i DiVA. Abstract. Miniaturized optogalvanic spectroscopy shows excellent prospects of becoming a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
(52 reference statements)
0
6
0
Order By: Relevance
“…At each step, the voltage between the electrodes and the probe, as well as the external pressure and flow rate were recorded. These parameters were chosen with respect to the first intended application of the device, which was to monitor the plasma inside a detector for optogalvanic spectroscopy 5 . In this application, pressures below 6 Torr and flows rates below 15 sccm are of particular interest 12 .…”
Section: Figure 2 Schematic View Of the Measurement Scheme Showing Amentioning
confidence: 99%
See 2 more Smart Citations
“…At each step, the voltage between the electrodes and the probe, as well as the external pressure and flow rate were recorded. These parameters were chosen with respect to the first intended application of the device, which was to monitor the plasma inside a detector for optogalvanic spectroscopy 5 . In this application, pressures below 6 Torr and flows rates below 15 sccm are of particular interest 12 .…”
Section: Figure 2 Schematic View Of the Measurement Scheme Showing Amentioning
confidence: 99%
“…The first intended application of the device is in a system for optogalvanic spectroscopy 4,5,19 where the pressure and flow rate generally is restricted to levels below 6 Torr and 15 sccm. Figure 6 shows the sensor performance in this domain, where the starting pressure was varied in nine steps between 1.1 Torr and 4.1 Torr.…”
Section: Voltage Difference Between the First Upstream And Downstrementioning
confidence: 99%
See 1 more Smart Citation
“…Our research group has previously demonstrated the possibility to perform stable isotope measurements [14] with a partly miniaturized system [15] based on a stripline splitring resonator (SSRR) microplasma source [16], which had some major advantages with respect to electromagnetic compatibility and interference [16], noise equivalent absorption sensitivity and minimum detectable absorption [14], and integrability with other functionality [17]. It was used in a measurement scheme called optogalvanic spectroscopy where isotopes could be detected by illuminating the discharge with laser light in resonance with one of the isotope-specific rovibrational states of the investigated molecule (in this case 12/13 CO 2 ) [18]. The isotope abundances could then be quantified by studying the change in plasma impedance that the excited molecules caused.…”
Section: Introductionmentioning
confidence: 99%
“…Integrating isolation valves in HTCC, is a step towards realizing a lab on a chip using this technology. Presented in [16], is an example of an ongoing effort to make an HTCC lab-on-a-chip for space applications. Among other components, this chip integrates the microplasma source and the microcombustor presented in [14] and [15], respectively, and is an application foreseen for the valve presented here.…”
Section: Introductionmentioning
confidence: 99%